Comparative Analysis of Peanut Farming Income Using Traditional Methods and Tugal in Tondong Tallasa Subdistrict, Pangkep Regency - Azzahratul Faisya; Reni Fatmasari Syafruddin; Hasriani Hasriani; Muh. Arifin Fattah; Isnam Junais (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
This study aims to analyze farmers’ income and compare the income from peanut farming using traditional planting methods and planting methods using a planting tool in Lanne Village, Tondong Tallasa Subdistrict, Pangkep Regency. This study employed a quantitative approach using a survey method. Sampling was conducted using purposive sampling—that is, by establishing specific criteria—resulting in 40 respondents, consisting of 20 peanut farmers using traditional planting methods and 20 farmers using a planting tool. The results showed that the average income from groundnut farming using traditional planting methods was Rp24,119,084 per growing season, with average revenue of Rp31,625,000 and average production costs of Rp7,505,916 per growing season. Meanwhile, the average income from peanut farming using the tugal planting tool was Rp25,456,051 per growing season, with average revenue of Rp31,750,000 and average production costs of Rp6,293,949 per growing season. This difference in income indicates that the use of the tugal planting tool can generate higher income compared to traditional planting methods, primarily due to labor cost efficiency. The results of the statistical analysis using an independent samples t-test show that the calculated t-value of 26.678 is greater than the critical t-value of 1.669 at a 95% confidence level. This indicates that there is a statistically significant difference in peanut farm income between the traditional planting method and the planting method using a tugal tool.